A Systems Biology Approach Identifies B Cell Maturation Antigen (BCMA) as a Biomarker Reflecting Oral Vaccine Induced IgA Antibody Responses in Humans - Mottram, Lynda; Lundgren, Anna; Svennerholm, Ann-Mari; Leach, Susannah (Frontiers in Immunology, 2021)
Vaccines against enteric diseases could improve global health. Despite this, only a few oral vaccines are currently available for human use. One way to facilitate such vaccine development could be to identify a practical and relatively low cost biomarker assay to assess oral vaccine induced primary and memory IgA immune responses in humans. Such an IgA biomarker assay could complement antigen-specific immune response measurements, enabling more oral vaccine candidates to be tested, whilst also reducing the work and costs associated with early oral vaccine development. With this in mind, we take a holistic systems biology approach to compare the transcriptional signatures of peripheral blood mononuclear cells isolated from volunteers, who following two oral priming doses with the oral cholera vaccine Dukoral, had either strong or no vaccine specific IgA responses. Using this bioinformatical method, we identify TNFRSF17, a gene encoding the B cell maturation antigen (BCMA), as a candidate biomarker of oral vaccine induced IgA immune responses. We then assess the ability of BCMA to reflect oral vaccine induced primary and memory IgA responses using an ELISA BCMA assay on a larger number of samples collected in clinical trials with Dukoral and the oral enterotoxigenic Escherichia coli vaccine candidate ETVAX. We find significant correlations between levels of BCMA and vaccine antigen-specific IgA in antibodies in lymphocyte secretion (ALS) specimens, as well as with proportions of circulating plasmablasts detected by flow cytometry. Importantly, our results suggest that levels of BCMA detected early after primary mucosal vaccination may be a biomarker for induction of long-lived vaccine specific memory B cell responses, which are otherwise difficult to measure in clinical vaccine trials. In addition, we find that ALS-BCMA responses in individuals vaccinated with ETVAX plus the adjuvant double mutant heat-labile toxin (dmLT) are significantly higher than in subjects given ETVAX only. We therefore propose that as ALS-BCMA responses may reflect the total vaccine induced IgA responses to oral vaccination, this BCMA ELISA assay could also be used to estimate the total adjuvant effect on vaccine induced-antibody responses, independently of antigen specificity, further supporting the usefulness of the assay.